Behaviour of the European Corn Borer, Ostrinia nubilalis Hb., on transgenic corn (Bollettino di zoologia agraria e bachicoltura, 2024)
The results of test carried out against the European Corn Borer are described. The latter tests was carried out in a confined environment with the aid of artificial infestations. The influence of transgenic corn on infestation, activity and development of the species is underlined. A very good protection rate of transgenic corn was noticed. An increase of the survival rate could be observed while the plants were approaching maturity without less yield. The reduction in insecticidal efficacy can be attributed more to the phenology of the plant and its correlated larval distribution than to a lower self protection of the hybrid. The time course of the survival of the larvae explains why the transgenic plants are very well protected during the stages of development during which the insects would otherwise severely impact on yield. It was also noticed that larvae that could survive had their development delayed, though this delay did not prevent the completion of their development cycle.
Keywords: Transgenic corn; corn self protection; Ostrinia nubilalis